BIOSYNTHESIS AND CHARACTERISATION OF SILVER (Ag) NANOPARTICLES USING TAGETES ERECTA LEAVES AND ITS LARVICIDAL EFFICACY AGAINST ANOPHELES MOSQUITOES - T. P, AYIM,; K. P, YORIYO,; P, AYIM,; J. O. , AYIM,; A, OMBUGADU, (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
Vector control is an essential requirement in any attempt to curtail vector-borne diseases like; malaria, filariasis, dengue etc. that are particularly transmitted by different species of mosquitoes. Sequel to the above, the study evaluated the biosynthesized silver nanoparticles (AgNPs) and the aqueous extract of T. erecta for its efficacy against Anopheles mosquitoes following the World Health Organization guidelines for laboratory testing of mosquito larvicides. Synthesized silver nanoparticles (AgNPs) were characterized by UV-visible, FTIR spectroscopy and SEM. Larvae of mosquitoes were collected from their original breeding site between the months of June and July 2021. Mature fresh leaves of T. erecta were collected from Igwo village, Obudu Local Government of Cross River State, Nigeria. The leaves were cleaned, washed and cool-dried for two weeks at room temperature. The larvae were exposed to 20, 40, 60, 80 and 100 mg/ml concentrations at 24-, 48- and 72-hours exposure period. Anopheles larvae were susceptible (100 %) to both the aqueous extract and the biosynthesized silver nanoparticles (AgNPs) of T. erecta plant at the highest concentrations (100 mg/ml). There was a very high significance (P<0.05) in the mortality rates of the larvae of mosquitoes in relation to concentrations. LC50 and LC90 values of the aqueous extract for 72 hours were 5.13 mg/ml and 28.18mg/ml while the LC50 and LC90 values of the biosynthesized silver nanoparticles (AgNPs) for 72 hours were 12.59 mg/ml and 44.67 mg/ml. Hence, the aqueous extract revealed a superior efficacy against the larvae of Anopheles mosquitoes. The study, therefore, supports the use of the extracts of T. erecta as alternatives to synthetic insecticides in the control of Anopheles mosquitoes.